2003
DOI: 10.1002/crat.200310117
|View full text |Cite
|
Sign up to set email alerts
|

Study on rapid growth of highly‐deuterated DKDP crystals

Abstract: Highly-deuterated potassium dihydrogen phosphate (DKDP) crystals were grown rapidly from point seeds under high supersaturation in a temperature range of 40-60 o C. The growth rate was about 1-2 order of magnitude higher than that of the traditional temperature reduction method. It was found that highly pure raw materials, overheating at high temperature, ultrafine filtration and supersaturation stability were needed to keep the solution from spontaneous nucleation at high overcooling. The effect of growth con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 9 publications
(14 reference statements)
0
8
0
Order By: Relevance
“…Potassium dihydrogen phosphate (KDP) and its deuterated analog DKDP are two of the most important nonlinear materials and the only one that can be grown to very large size [1] . In the third harmonic generation (THG) of Nd:glass laser, DKDP is preferred used to substitute KDP crystal for its weak stimulated Raman scattering (SRS) effect [2][3] . However, for the traditional temperature-reduction method of DKDP crystal growth, the growth rate is merely 0.5-1 mm/day which leads to growth cycles exceeding 1-2 years.…”
Section: Introductionmentioning
confidence: 99%
“…Potassium dihydrogen phosphate (KDP) and its deuterated analog DKDP are two of the most important nonlinear materials and the only one that can be grown to very large size [1] . In the third harmonic generation (THG) of Nd:glass laser, DKDP is preferred used to substitute KDP crystal for its weak stimulated Raman scattering (SRS) effect [2][3] . However, for the traditional temperature-reduction method of DKDP crystal growth, the growth rate is merely 0.5-1 mm/day which leads to growth cycles exceeding 1-2 years.…”
Section: Introductionmentioning
confidence: 99%
“…The ICF project chooses large-aperture, highly deuterated DKDP crystals as electro-optic switch materials [9] . However, the growth of large-size, 98%-deuterated DKDP crystals faces many difficulties, such as disturbance of the monoclinic DKDP crystal during the growth of the tetragonal DKDP crystal, hydrogen–deuterium exchange, and the need for expensive heavy water [8, 10] . To date, there have been very few reports on the growth of highly deuterated DKDP crystals.…”
Section: Introductionmentioning
confidence: 99%
“…[8] reported that DKDP crystals with a deuterium content of 98% and sizes of were successfully grown by point-seed technology. The tetragonal-to-monoclinic solubility transition can be avoided by the rapid-growth technique [10] . It is essential that a rapid-growth method is used for the growth of highly deuterated DKDP crystals by the point-seed technique.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations